Correlations Between the Monoaminergic Status and the Psychoneuroendocrine Typology in a Murine Model – Possible Biomolecular Predictions for an Individualized Pharmacotherapy - Arsene, Andreea Letitia; Mitrea, Niculina; Lupuliasa, Dumitru (IntechOpen, 2012)
None